Heat Transfer, Volume 2 2004
DOI: 10.1115/imece2004-61753
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Enhanced Surface Spray Cooling

Abstract: Phase change technology is a science that is continually finding new applications, from passive refrigeration cycles to semiconductor cooling. The primary heat transfer techniques associated with phase change heat transfer are pool boiling, flow boiling, and spray cooling. Of these techniques, spray cooling is the least studied and the most recent to receive attention in the scientific community. Spray cooling is capable of removing large amounts of heat between the cooled surface and the liquid, with reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Other topics researched to date include the effect of surfactant addition [12,13], and secondary nucleation [ 1, 14,15]. This work is a continuation of the enhanced surface study by Silk et al [16], with an emphasis on cubic pin fins as the basic geometric feature of the surface enhancement, The objective of the current work is to examine the effects of these geometries and their arrangement on heat flux when using spray Most previous studies that have examined enhanced surfaces have done so primarily from the perspective of surface roughness. Sehmbey et al [l] gives an overview of spray cooling and provides a comparison of its effectiveness when using liquid and secondary gas atomizers (air used as the secondary gas).…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…Other topics researched to date include the effect of surfactant addition [12,13], and secondary nucleation [ 1, 14,15]. This work is a continuation of the enhanced surface study by Silk et al [16], with an emphasis on cubic pin fins as the basic geometric feature of the surface enhancement, The objective of the current work is to examine the effects of these geometries and their arrangement on heat flux when using spray Most previous studies that have examined enhanced surfaces have done so primarily from the perspective of surface roughness. Sehmbey et al [l] gives an overview of spray cooling and provides a comparison of its effectiveness when using liquid and secondary gas atomizers (air used as the secondary gas).…”
Section: Introductionmentioning
confidence: 49%
“…The initial work by Silk et al [16] showed that spray cooling of enhanced structure surfaces results in a corresponding heat flux enhancement. The present work investigates spray cooling heat flux as a hnction of cubic pin fin geometry and structure arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Mudawar [7]- [9] designed an R134a-cooled two-phase microchannel heat sink capable of providing a heat transfer coefficient up to 50 000 W/m 2 -K. Fabbri et al [10] developed a single-phase spray-cooling system showing that a heat transfer coefficient of 15 000 W/m 2 -K can be obtained with the water as the working fluid. Silk et al [11] demonstrated that a two-phase spray cooling with PF-5060 as the working fluid can achieve a heat transfer coefficient of 24 000 W/m 2 -K. Compared to microchannel cooling and spray cooling, jet impingement cooling can offer much higher heat transfer capability. For example, Natarajan and Bezama [12] demonstrated that a single-phase water submerged jet can reach a heat transfer coefficient as high as 52 000 W/m 2 However, these high heat flux cooling solutions, when applied on the back side of the direct-bonded copper (DBC) substrate and designed for thermal management of the entire IGBT module, cannot remove the nonuniform temperature distribution on the individual IGBT chips.…”
Section: Introductionmentioning
confidence: 98%
“…The very high spray efficiencies observed in this study are likely due to the small scale of the microchannels along with the relative sparseness of the spray. It may likely be confirmed that given a greater flow rate, the heat transfer could be improved at the expense of a decreased spray efficiency as shown by Pautsch and Shedd (2005) with flat surfaces and Silk et al (2004Silk et al ( , 2005 with enhanced surfaces. However, spraying microchannels with a sparse spray may be one way of improving thermal performance without merely increasing the mass flow rate, which can be expensive in terms of pump power, cost, and weight.…”
Section: Two-phase Effectsmentioning
confidence: 94%
“…However, recent studies have indicated that enhanced surfaces with large-scale roughness elements (greater than the liquid film thickness) have the potential to transfer as much as 50% more heat than comparable flat surfaces. Most recently, Silk et al (2004Silk et al ( , 2005 investigated spraying gassy (1 atm) PF-5060 on a flat surface and enhanced surfaces including straight fins, square pin fins, and pyramidal fins. They used a 2×2 Parker Hannefin nozzle array with a volumetric flux of 0.016 m 3 /(m 2 ·s).…”
Section: Introductionmentioning
confidence: 99%